Analisis Konsep Pemasaran Yang Digunakan Oleh Para Pedagang - Nurul Fitri Amanda; Rahmi Andini Nst; Evan R Manurung (Al-Sharf: Jurnal Ekonomi Islam, 2020)
This research was conducted to obtain information about the marketing strategies used by traders, market competition and increase income. In relation to this research, in general, the traders on average junior high school (SMP) graduates have minimal knowledge of marketing strategies but are able to survive in market competition and traders are also able to reap a lot of profit, the level of competitiveness of similar goods is very much. The research was conducted in qualitative research with descriptive form and the subjects taken from the research source were Fried, Noodle, and Packaged Rice Traders which consisted of some information that handled interview techniques that were DAPT, INTERVIEW and DOCUMENTATION and data analysis using SWOT analysis. The results of research with indicators of product, price and distributor strategies indicate that traders are implementing quality improvements, product characteristics, product packaging, and trading models. Positioning products through packaging prices to consumers and production, relying on strategic locations, convenience of consumers and production places, relying on strategic locations, comforting places for consumers and using direct promotions due to limited knowledge of traders about marketing strategies. In Alternative PK, maintain quality and quantity product increase promotion, improve sales management system and maintain good relations with consumers and increase the variety of competent products.keyword: merchant, SWOT, product